The crimes of terrorism and its consequences for international peace and security "Crimes Condemned Model" - المدرس امركخِر َێىي غتراهلل وحىر; امىررس امىساغر سٍروەر حىٍ احىر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Terrorism is one of the most contemporary and serious issues that faces all the countries and international communities in the world, and which has garnered great attention from most international communities due to the fact that it creates massive threat on the peace and tranquility of international and local communities. Nowadays the Islamic State of Iraq and Levant, as known by ISIS/ISIL is the harbinger of the modern terror on a regional level and specifically in Iraq and Syria. This research aims to concentrate on the main threats and the impact of ISIL on international peace and security. As well as aiming to shed light on the role of both Security Council of the United Nations and the international criminal court in facing terror. This research is under the title of: crimes of terrorism, threats and its impacts on international peace and security, using ISIL as a case study. Essentially the body structure consists of the introduction, four chapters, conclusion, and references. The first chapter concentrates on the most common definitions of terrorism and understanding crimes of terrorism. The second chapter entirely focuses on The Islamic State of Iraq and the Levant as known by ISIS/ISIL/Dae’sh. The third chapter discusses the main threats of ISIL on international peace and security. Ultimately, the fourth chapter including the conclusion focuses on the role of international administrations in facing and eliminating terror.